Building the Case for A Single Key Informant in Supply Chain Management Survey Research. Issue 1 (8th December 2017) - Krause, Daniel; Luzzini, Davide; Lawson, Benn
Abstract : Survey research is appropriate and necessary to address certain types of research questions. In this paper, we acknowledge the ongoing debate about survey research and focus specifically on examining the conditions under which a study might validly utilize data provided by a single respondent. To this end, we summarize the main challenges that survey research in supply chain management faces when dealing with single respondents and later argue that having multiple respondents does not necessarily represent a cure‐all solution. Next, we discuss the concept of alignment in survey research and explore the characteristics of research questions that can be addressed through single key informants. We conclude the paper by suggesting that researchers should carefully consider the appropriateness of single key informants in light of the type of research question and also clearly support such choice when describing the method adopted.